Prodependence vs. Codependency: Would a New Model (Prodependence) for Treating Loved Ones of Sex Addicts Be More Effective Than the Model We've Got (Codependency)?. Issue 3 (2nd October 2019) - Weiss, Robert
Abstract: Spouses, partners, parents, and other loved ones of sex addicts are generally treated with variations of the codependency model, which, in a general way, fails to acknowledge that these individuals are in the midst of a relational crisis. Prodependence is a new paradigm for addressing this clientele. Grounded in attachment rather than trauma theory, prodependence views what has previously been seen as dysfunctional (trying to help and stay connected with a sex addict) as how any rational person would act when presented with the extraordinary life crisis of a struggling family member. As an initial evaluation of this new paradigm, clinicians who treat this population were surveyed before and after an informal educational presentation explaining the prodependence model and how it differs from codependency. Findings showed that clinicians currently tend to use variations of codependency in their practices, although many expressed dissatisfaction with this approach. After exposure to the prodependence paradigm, the majority of clinicians expressed a desire to move away from codependency in favor of the prodependence model. This suggests that the attachment and crisis-centric model of prodependence could be more effective than codependency when working with loved ones of sex addicts (and perhaps loved ones of other addicts).